Effects of the PLK4 inhibitor Centrinone on the biological behaviors of acute myeloid leukemia cell lines - Mu, Xing-Ru; Ma, Meng-Meng; Lu, Zi-Yi; Liu, Jun; Xue, Yu-Tong; Cao, Jiang; Zeng, Ling-Yu; Li, Feng; Xu, Kai-Lin; Wu, Qing-Yun (Frontiers in Genetics, 2022)
Polo-like kinase 4 (PLK4), a key regulator of centriole biogenesis, is frequently overexpressed in cancer cells. However, roles and the mechanism of PLK4 in the leukemogenesis of acute myeloid leukemia (AML) remain unclear. In this study, the PLK4 inhibitor Centrinone and the shRNA knockdown were used to investigate roles and mechanisms of PLK4 in the leukemogenesis of AML. Our results showed that Centrinone inhibited AML cell proliferation in a concentration- and time-dependent manner via inhibited PLK4 expression both in the protein and mRNA levels. Moreover, colony formation assays indicated that Centrinone reduced the number and the size of the AML colonies. Centrinone induced AML cell apoptosis by increasing the activation of Caspase-3/poly ADP-ribose polymerase (PARP). Notably, Centrinone caused the G2/M cell cycle arrest by decreasing the expression of cell cycle-related proteins such as Cyclin A2, Cyclin B1, and Cyclin-dependent kinases 1 (CDK1). Consistent with the above results, knocdown the expression of PLK4 also inhibited cell proliferation and clonogenic ability, induced cell apoptosis, and caused G2/M cell cycle arrest without affecting cell differentiation. All in all, this study implied that PLK4 inhibited the progression of AML in vitro, and these results herein may provide clues in roles of PLK4 in the leukemogenesis of AML.